1992
DOI: 10.1200/jco.1992.10.4.529
|View full text |Cite
|
Sign up to set email alerts
|

Significance of epidermal growth factor receptor in advanced ovarian cancer.

Abstract: Data reported here suggest that the presence of EGF-R in advanced ovarian tumor at the time of the primary surgery identifies a subset of patients with a particularly poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(45 citation statements)
references
References 29 publications
2
42
0
1
Order By: Relevance
“…Whereas the frequency of ErbB2 overexpression is low, the frequencies of ErbB3 and ErbB4 expressions are high in OVCA. Univariate and multivariate statistical analyses have confirmed that EGFR overexpression is significantly associated with a high risk of progression in OVCA patients (Scambia et al, 1992). Seven ligands have been described for EGFR: EGF, transforming growth factor-a (TGF-a).…”
mentioning
confidence: 97%
“…Whereas the frequency of ErbB2 overexpression is low, the frequencies of ErbB3 and ErbB4 expressions are high in OVCA. Univariate and multivariate statistical analyses have confirmed that EGFR overexpression is significantly associated with a high risk of progression in OVCA patients (Scambia et al, 1992). Seven ligands have been described for EGFR: EGF, transforming growth factor-a (TGF-a).…”
mentioning
confidence: 97%
“…Ovarian tumors are pathologically heterogeneous, and although the initiating events in ovarian tumor development are poorly understood, ovarian tumorigenesis is characterized by multiple genetic alterations and molecular signatures (2). The epidermal growth factor (EGF) receptor (EGFR) is overexpressed or mutated in a wide variety of human tumors including ovarian carcinomas (3)(4)(5)(6)(7)(8). Cellular responses to EGFR activation include those that play a critical role in tumor growth, survival, and progression, whereas EGFR overexpression in tumors has been associated clinically with progression and metastasis (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Both c-erbB-1 (EGFR) and c-erbB-2 overexpression have been associated with aggressive behaviour in a series of solid tumours, including breast (Sainsbury et al, 1987;Slamon et al, 1989), cervix (Gullick et al, 1988Pfeiffer et al, 1989) and ovary (Bauknecht et al, 1988;Berchuck et al, 1990;Scambia et al, 1992). In contrast, considerably less is known about the involvement of c-erbB-3 in malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Gene amplification and protein overexpression of receptor tyrosine kinases including the epidermal growth factor receptor (EGFR) and c-erbB-2 protein have been associated with the induction and progression of a number of human cancers (Sainsbury et al, 1987;Bauknecht et al, 1988;Gullick et al, 1988;Slamon et al, 1989;Berchuck et al, 1990Berchuck et al, , 1991Scambia et al, 1992). A relatively new member of this type I growth factor receptor family, c-erbB-3, has also been characterised (Kraus et al, 1989;Plowman et al, 1990), although clarification of its biological role awaits identification of a specific ligand.…”
mentioning
confidence: 99%